KESADARAN HUKUM KONSUMEN MUSLIM PEMBELI RAGI TERHADAP REGULASI PRODUK BERLABEL HALAL DI PASAR WIRADESA KABUPATEN PEKALONGAN - Arina Manasikana; Karimatul Khasanah; Heny Rahmawati (el hisbah: Journal of Islamic Economic Law, 2022)
Yeast sold at Wiradesa Market does not yet include a halal label on its products. However, in reality, in Wiradesa Market, yeast products that have not been labeled as halal are still in great demand by Muslim consumers. This study aims to determine the legal awareness of Muslim consumers regarding product regulations that must be labeled as halal and to determine the factors that influence the level of legal awareness of consumers buying yeast in the Wiradesa market. The results of this study indicate that the legal awareness of Muslim consumers buying yeast in the Wiradesa market is low. Indicators of legal knowledge and understanding are not fulfilled due to the ignorance of the public, especially yeast buyers, regarding the regulation of halal product guarantees. Regulations that are not understood by Muslim consumers buying yeast at the Wiradesa Market also affect legal attitudes and legal behavior of consumers who do not pay attention to whether the yeast product they buy is halal certified or vice versa. While the factors that influence the level of legal awareness of Muslim consumers are influenced by two factors. The first is the education factor, the consumer informants in this research are still in the low-educated category. Second, the price factor, namely by choosing cheap yeast prices.